Konstribusi Faktor Self Assessment dan Peer Assessment terhadap Kecemasan dalam Menghadapi Ujian OSCE Mahasiswa Keperawatan - Ari Kresna Dewi, Ni Luh Gede; Suardani, Ni Luh Ketut (Jurnal Gema Keperawatan, 2025)
Anxiety is a normal part of life. Excessive anxiety responses can affect exam performance and results. The OSCE is a comprehensive assessment of students' clinical competency. Final-semester nursing students are required to take the OSCE exam according to standards. With more exam material and different exam settings, this situation creates anxiety in students before the OSCE. The graduation rate of the Nursing Department of the Ministry of Health Polytechnic of Denpasar in 2024 reached 97,3% for the Nursing study program and 87.06% for the Diploma III study program. Therefore, it is deemed necessary to evaluate learning outcomes, which can be done independently (self-assessment) or assessed by group members (peer assessment), to prevent abnormal anxiety in students and achieve optimal passing scores. The purpose of this study was to analyze the contributors of self- and peer assessment factors to student anxiety in facing the OSCE exam. This study used a quantitative descriptive design. The number of respondents was 60 respondents, with a simple random sampling technique. The variables examined in this study were the anxiety levels of students who received self-assessment, peer assessment, and self- and peer assessment interventions. The research instrument used was the Hamilton Rating Scale for Anxiety (HRS-A) questionnaire. The Kruskal-Wailiss test was used to analyze the results, resulting in a mean anxiety rank of 26,10. The conclusion was that the most effective intervention was a combination of self- and peer assessment.